2002
DOI: 10.1093/jac/dkf145
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in vitro activity of garenoxacin against Chlamydia spp.

Abstract: The in vitro susceptibilities of 33 isolates of Chlamydia trachomatis, Chlamydia pneumoniae and Chlamydia psittaci to a new quinolone drug, garenoxacin (BMS-284756), in comparison with levofloxacin, ciprofloxacin, doxycycline, erythromycin and roxithromycin, were determined. Garenoxacin was the most active of the quinolone drugs tested, with identical MIC and MBC, which ranged from 0.007 to 0.03 mg/L. The MIC and MBC of the other two quinolones tested, levofloxacin and ciprofloxacin, were also identical, rangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…However, C. pneumoniae growing in the polarized Calu-3 cultures appeared to be very resistant to doxycycline exposure (MBC Ͼ 2 g/ml), whereas in the flat Calu-3 cultures, an MBC as low as 0.06 g/ml was detected. The inhibitory concentrations are in accordance with those reported earlier for some C. pneumoniae isolates (10) but are somewhat higher than the more recently reported doxycycline MIC values for C. pneumoniae (2,34), most probably due to the different evaluation methods used.…”
Section: Vol 78 2010 C Pneumoniae Infection In Polarized Epitheliasupporting
confidence: 91%
“…However, C. pneumoniae growing in the polarized Calu-3 cultures appeared to be very resistant to doxycycline exposure (MBC Ͼ 2 g/ml), whereas in the flat Calu-3 cultures, an MBC as low as 0.06 g/ml was detected. The inhibitory concentrations are in accordance with those reported earlier for some C. pneumoniae isolates (10) but are somewhat higher than the more recently reported doxycycline MIC values for C. pneumoniae (2,34), most probably due to the different evaluation methods used.…”
Section: Vol 78 2010 C Pneumoniae Infection In Polarized Epitheliasupporting
confidence: 91%
“…Macrolides exhibit excellent in vitro activity against atypical respiratory pathogens, and have traditionally been considered drugs of first choice for infections due to atypical pathogens [15][16][17][18][19][20][21][22][23]. Against contemporary isolates of C. pneumoniae, the minimum inhibitory concentration minimal inhibitory concentration of 90% bacteria values of the macrolides (erythromycin, roxithromycin, clarithromycin and azithromycin) are typically in the range of 0.016-0.5 mg?L -1 [15,21,22,24,25].…”
Section: In Vitro Susceptibilitymentioning
confidence: 99%
“…However, their in vitro potency is often inferior to that of the macrolides and fluoroquinolones [15,16,19,23]. Furthermore, there is evidence to suggest that strains of M. pneumoniae are developing resistance to tetracycline [23].…”
Section: In Vitro Susceptibilitymentioning
confidence: 99%
“…The methods used in those studies either differed from those used in our study or were not reported, and therefore, a comparison of the results must be made with caution because of possible methodological differences (11,24). However, all garenoxacin MICs reported have ranged from Ͻ0.008 to 0.015 g/ml, and MBCs were equal to the MIC or were 1 twofold dilution higher, while the levofloxacin and moxifloxacin MICs were higher, usually 2 to 5 twofold dilutions for MIC testing (8,9,27).…”
Section: Discussionmentioning
confidence: 57%
“…Three isolates tested in both studies had the same susceptibilities in both studies. Three other studies reported on the garenoxacin MICs for small numbers of C. pneumoniae isolates (8,9,27). The methods used in those studies either differed from those used in our study or were not reported, and therefore, a comparison of the results must be made with caution because of possible methodological differences (11,24).…”
Section: Discussionmentioning
confidence: 78%